Biochar for modifying sulphoaluminate cement and preparation method thereof
By dry mixing the biochar prepared by hydrothermal reaction and pyrolysis with sulfaaluminate cement with sulfaaluminate cement, the problem of slow or even reverse strength increase in the later stage of the sulfaaluminate cement is solved, and the effect of improving compressive strength and absorbing biomass solid waste is achieved.
Patent Information
- Application Number
- CN202510321249.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-06-27
AI Technical Summary
Sulfur aluminate cement quickly produces ettringite in the early stage during hydration, resulting in slower and even reversed strength increase in the later stage. The existing modification methods are complex and costly.
By mixing the fruit wood residue and iron-containing sludge for hydrothermal reaction and pyrolysis, biochar of modified sulfaaluminate cement with rich pore structure and oxygen-containing functional groups was prepared, and the sulfaaaluminate cement was mixed with dry mix.
It effectively solves the problem of slow or even reverse strength increase in the later stage of sulfoaluminate cement, improves its compressive strength, and is simple in preparation and low-cost, which can greatly absorb biomass solid waste.
Smart Images

Figure CN120208194A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cement modifiers, and particularly to a biochar for modifying sulphoaluminate cement and a preparation method thereof. Background Art
[0002] The information disclosed in the background art of the present invention is only intended to increase the understanding of the overall background of the present invention, and is not necessarily regarded as an admission or an implication in any form that this information constitutes the prior art already known to those of ordinary skill in the art.
[0003] Sulphoaluminate cement has the characteristics of rapid hardening, early strength, high strength, high frost resistance, high impermeability, etc., and is particularly suitable for wide application in marine engineering and grouting engineering. However, during the hydration process of sulphoaluminate cement, ettringite (AFt) is rapidly generated in the early stage (1 - 3 days), but after 7 days, AFt gradually transforms into monosulphoaluminate (AFm), resulting in a decrease in structural compactness, a stagnation or even a decrease in strength growth, and a reverse shrinkage of the later strength. Therefore, it is necessary to modify sulphoaluminate cement to improve its later strength without significantly affecting its original properties. Currently, technical solutions for modifying sulphoaluminate cement during the production process have been reported. For example, the patent with the authorization announcement number CN112608047B discloses a preparation method for modifying sulphoaluminate cement, which is to mix a lithium salt with the raw materials of sulphoaluminate cement, calcine at a high temperature for 30 - 60 minutes, and rapidly cool to room temperature to obtain a lithium salt-modified cement clinker, and then mix the cement clinker with gypsum and grind it to finally obtain the modified sulphoaluminate cement. Although this method effectively improves the performance of sulphoaluminate cement, its raw materials and preparation method are complex. Therefore, it is very necessary to improve the performance of sulphoaluminate cement in a simple blending manner. The patent with the authorization announcement number CN117401917B discloses a method for modifying sulphoaluminate cement with high-purity lithium sulfate crystals extracted from waste lithium batteries, which can further promote the setting of sulphoaluminate cement and enhance its early strength, but it does not mention the problem of strength reverse shrinkage of sulphoaluminate cement, and at the same time, the recovery process of its modifier lithium sulfate has many steps.
[0004] Therefore, how to provide a modifier that can achieve the consumption of solid waste resources, can improve the later strength of sulphoaluminate cement in a simple blending manner, and has a low preparation cost is an urgent problem to be solved. Summary of the Invention
[0005] In view of this, the present invention provides a biochar for modifying sulphoaluminate cement and a preparation method thereof. The preparation method of the biochar for modifying sulphoaluminate cement provided by the present invention is simple, can achieve the large-scale consumption of solid waste, and can effectively solve the problem of slow or even reverse shrinkage of the later strength of sulphoaluminate cement.
[0006] In a first aspect, the present invention provides a method for preparing biochar of modified sulfoaluminate cement, comprising the following steps:
[0007] Mix fruit tree residue and iron-containing sludge, add water, and carry out hydrothermal reaction at 200-250 °C. After the reaction is completed, filter and dry to obtain a hydrothermal carbon material; then pyrolyze the hydrothermal carbon material under an inert atmosphere at a pyrolysis temperature of 700-900 °C to obtain the biochar of modified sulfoaluminate cement.
[0008] In a second aspect, the present invention provides the biochar of modified sulfoaluminate cement prepared by the above preparation method.
[0009] In a third aspect, the present invention provides a modified sulfoaluminate cement, comprising sulfoaluminate cement and 0.5-2 wt% of the biochar of the above modified sulfoaluminate cement.
[0010] In a fourth aspect, the present invention provides the preparation method of the above modified sulfoaluminate cement, comprising the following steps:
[0011] Dry-mix and mix the sulfoaluminate cement and the biochar of the modified sulfoaluminate cement to obtain the product.
[0012] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0013] The present invention mixes the huge-output biomass solid waste fruit tree residue and iron-containing sludge, and prepares a carbon material with a rich pore structure, oxygen-containing functional groups and iron elements through two steps of hydrothermal carbonization and pyrolytic carbonization. Using it as the biochar of modified sulfoaluminate cement can facilitate the continuous hydration reaction of sulfoaluminate cement, thereby achieving the effect of continuously enhancing the compressive strength of sulfoaluminate cement, and at the same time has no impact on the setting performance of sulfoaluminate cement. The method of the present invention can not only greatly consume biomass solid waste, but also improve the compressive strength of sulfoaluminate cement in a low-cost and simple manner, and effectively inhibits the late strength retrogression phenomenon of sulfoaluminate cement, having good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] The specification drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.
[0015] Figure 1 It is a schematic process flow diagram of the preparation of the biochar of the modified sulfoaluminate cement in Examples 1-4 of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0016] It should be noted that the following detailed description is exemplary and is intended to provide further illustration of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present invention pertains.
[0017] The present invention provides a method for preparing biochar of modified sulphoaluminate cement, comprising the following steps:
[0018] Mix fruit tree residue and iron-containing sludge, add water, and carry out hydrothermal reaction at 200 - 250 °C. After the reaction is completed, filter and dry to obtain a hydrothermal carbon material; then pyrolyze the hydrothermal carbon material in an inert atmosphere at a pyrolysis temperature of 700 - 900 °C to obtain the biochar of modified sulphoaluminate cement.
[0019] The present invention uses fruit tree residue and iron-containing sludge as raw materials, and both of these raw materials belong to biomass solid waste. During the co-hydrothermal treatment process, there is a synergistic effect between the fruit tree residue and the iron-containing sludge, which can synergistically improve the yield of hydrothermal carbon and the carbon fixation rate. At the same time, cellulose and lignin in the fruit tree residue can form a more complex carbon structure under the co-hydrothermal conditions, increasing the specific surface area and porosity of the hydrothermal carbon. When iron element is added as a chemical admixture to the cement paste, more ferrite phases are consumed, and the iron dissolved in the pore solution changes the initial hydration product layer, accelerating the hydration process, resulting in the formation of more calcium silicate hydrate gel (CSH gel) and a denser microstructure, thus being beneficial to continuously enhancing the strength of sulphoaluminate cement.
[0020] The present invention first conducts a hydrothermal reaction at 200 - 250 °C. The hydrothermal carbon material obtained by this method has abundant oxygen-containing functional groups and a certain amount of pore structure. Then, on the basis of the hydrothermal carbon material, the present invention further conducts high-temperature pyrolysis. This process can further increase the pore structure of the hydrothermal carbon material, which is beneficial to adsorbing free water and slowly releasing free water under specific environments. The slowly released free water can continuously react with the anhydrous calcium sulphoaluminate mineral in the sulphoaluminate cement to generate hydrated product ettringite (AFt) with micro-expansion characteristics, thereby continuously increasing the compactness of the hydrated paste and continuously enhancing the later strength of the hydrated paste of sulphoaluminate cement.
[0021] The fruit tree residue described in the present invention is a product obtained by crushing and grinding fruit tree branches. The fruit tree residue is subjected to screening treatment, and the screen size is 18 - 50 meshes. In one or more embodiments of the present invention, the screen size is 20 meshes. The fruit tree residue after screening treatment has a smaller particle size, which can have higher reaction activity in the subsequent hydrothermal reaction.
[0022] The iron-containing sludge of the present invention is preferably subjected to crushing treatment to increase its reaction area. In the iron-containing sludge, the mass fraction of iron element is 1-3%, and the water content of the iron-containing sludge is 60-90%. The present invention does not impose special restrictions on the source of the iron-containing sludge, and the content of the iron element therein is determined by inductively coupled plasma mass spectrometry (ICP-MS).
[0023] In the present invention, the mass ratio of the fruit wood residue to the iron-containing sludge is 1:(0.8-1.2). In one or more embodiments of the present invention, the mass ratio of the fruit wood residue to the iron-containing sludge is 1:1. The mass ratio of the total mass of the fruit wood residue and the iron-containing sludge to the mass of water is 1:(8-15).
[0024] In the present invention, the time of the hydrothermal reaction is 2-4 h. The hydrothermal reaction time affects the yield of hydrothermal carbon. With the prolongation of the hydrothermal reaction time, it is beneficial for the dissolved intermediate products to polymerize in the form of secondary hydrothermal carbon, but too long a holding time will also cause the decomposition of the carbon structure. Prolonging the holding time will also make the surface of the biochar more hydrophobic. This is mainly because the cracks and grooves on the surface of the biochar gradually turn into a smoother spherical structure after a long time of treatment, reducing the affinity between the biochar and water molecules, thereby enhancing its hydrophobicity.
[0025] The present invention does not impose special restrictions on the steps of filtration and drying, and the commonly used filtration and drying methods in the art can be adopted.
[0026] In the pyrolysis step of the present invention, the pyrolysis temperature is more preferably 750-850 °C, the pyrolysis time is 1.5-3 h, and more preferably 1.5-2.5 h. The heating rate for heating to the pyrolysis temperature is 5-15 °C / min, and more preferably 8-12 °C / min.
[0027] The inert atmosphere in the pyrolysis process of the present invention is selected from one or more of nitrogen or noble gases. In one or more embodiments of the present invention, the inert atmosphere is nitrogen.
[0028] The present invention also provides the biochar of the modified sulfoaluminate cement prepared by the above preparation method.
[0029] The present invention also provides a modified sulfoaluminate cement, which includes sulfoaluminate cement and 0.5-2 wt% of the biochar of the above modified sulfoaluminate cement. The above mass fraction refers to the mass fraction of the biochar of the modified sulfoaluminate cement in the modified sulfoaluminate cement. If the addition amount of the biochar of the modified sulfoaluminate cement is too low, it cannot effectively improve the performance. If the addition amount of the biochar of the modified sulfoaluminate cement is too high, it will have an adverse effect on the strength and setting time of the modified sulfoaluminate cement.
[0030] The present invention also provides a preparation method of the above-mentioned modified sulphoaluminate cement, which comprises the following steps:
[0031] Dry-mix and mix the sulphoaluminate cement and the biochar of the modified sulphoaluminate cement, and that's it.
[0032] The present invention does not impose special restrictions on the dry-mix mixing method, and the commonly used dry-mix mixing method in the art can be adopted. The present invention can obtain the modified sulphoaluminate cement only by simple dry-mix mixing. The preparation method is very simple and the cost is low.
[0033] The technical solution of the present invention will be further elaborated below in conjunction with specific embodiments.
[0034] In the following examples, the water content of the iron-containing sludge is 80%, and the iron element content in the iron-containing sludge is measured by inductively coupled plasma mass spectrometry (ICP-MS) to be 1.26 wt%.
[0035] Example 1
[0036] This example provides a biochar of modified sulphoaluminate cement and a preparation method of modified sulphoaluminate cement.
[0037] (1) Preparation of biochar of modified sulphoaluminate cement:
[0038] Crush the iron-containing sludge cake to obtain iron-containing sludge residue, and crush apple branches and pass through a 20-mesh sieve to obtain fruit wood residue. Mix the iron-containing sludge residue and the fruit wood residue in a mass ratio of 1:1, and mix the mixture of the two with water in a mass ratio of 1:10, and fully stir to obtain a sludge fruit wood residue turbid liquid.
[0039] Place the sludge fruit wood residue turbid liquid in a reaction kettle, raise the temperature to 200 °C at a heating rate of 5 °C / min for hydrothermal carbonization reaction, the reaction time is 2 h, the stirring rate is 400 rpm, and then cool it with circulating water. Filter and dry the hydrothermal product to obtain dry hydrothermal carbon.
[0040] Put the obtained dry hydrothermal carbon into a tubular furnace, carry out pyrolysis under a nitrogen atmosphere, the heating rate is 10 °C / min, the target temperature is 800 °C, keep warm for 2 h and then cool naturally to room temperature to obtain hydrothermal pyrolysis carbon, that is, the biochar of modified sulphoaluminate cement. The schematic diagram of the preparation process is as Figure 1 shown.
[0041] (2) Preparation method of modified sulphoaluminate cement:
[0042] Incorporate the biochar of the modified sulphoaluminate cement obtained in step (1) into the sulphoaluminate cement at an addition amount of 1 wt%, and dry-mix and mix to obtain the modified sulphoaluminate cement.
[0043] Example 2
[0044] This embodiment provides a biochar for modified sulfoaluminate cement and a preparation method for modified sulfoaluminate cement.
[0045] (1) Preparation of biochar for modified sulfoaluminate cement:
[0046] Crush the iron-containing sludge cake to obtain iron-containing sludge residue, and crush the fruit wood and sieve it through a 20-mesh sieve to obtain fruit wood residue. Mix the iron-containing sludge residue and the fruit wood residue in a mass ratio of 1:1, and mix the mixture of the two with water in a mass ratio of 1:10, and stir well to obtain a sludge-fruit wood residue turbid liquid.
[0047] Place the sludge-fruit wood residue turbid liquid in a reaction kettle, raise the temperature to 230 °C at a heating rate of 5 °C / min for hydrothermal carbonization reaction, the reaction time is 2 h, and the stirring rate is 400 rpm. Then cool it with circulating water, filter and dry the hydrothermal product to obtain dry hydrothermal carbon.
[0048] Put the obtained dry hydrothermal carbon into a tubular furnace, carry out pyrolysis under a nitrogen atmosphere, the heating rate is 10 °C / min, the target temperature is 800 °C, keep the temperature for 2 h and then cool it naturally to room temperature to obtain hydrothermal pyrolysis carbon, that is, the biochar for modified sulfoaluminate cement. The schematic diagram of the preparation process is as Figure 1 shown.
[0049] (2) Preparation method of modified sulfoaluminate cement:
[0050] Incorporate the biochar for modified sulfoaluminate cement obtained in step (1) into the sulfoaluminate cement at an addition amount of 1 wt%, and mix it dry to obtain the modified sulfoaluminate cement.
[0051] Example 3
[0052] This embodiment provides a biochar for modified sulfoaluminate cement and a preparation method for modified sulfoaluminate cement.
[0053] (1) Preparation of biochar for modified sulfoaluminate cement:
[0054] Crush the iron-containing sludge cake to obtain iron-containing sludge residue, and crush the fruit wood and sieve it through a 20-mesh sieve to obtain fruit wood residue. Mix the iron-containing sludge residue and the fruit wood residue in a mass ratio of 1:1, and mix the mixture of the two with water in a mass ratio of 1:10, and stir well to obtain a sludge-fruit wood residue turbid liquid.
[0055] Place the sludge-fruit wood residue turbid liquid in a reaction kettle, raise the temperature to 230 °C at a heating rate of 5 °C / min for hydrothermal carbonization reaction, the reaction time is 3 h, and the stirring rate is 400 rpm. Then cool it with circulating water, filter and dry the hydrothermal product to obtain dry hydrothermal carbon.
[0056] Put the obtained dry hydrothermal carbon into a tube furnace and pyrolyze it under a nitrogen atmosphere. The heating rate is 10 °C / min, the target temperature is 800 °C, and after holding for 2 h, it is naturally cooled to room temperature to obtain hydrothermally pyrolyzed carbon, that is, the biochar of modified sulfoaluminate cement. The schematic diagram of the preparation process is as Figure 1 shown.
[0057] (2) Preparation method of modified sulfoaluminate cement:
[0058] Mix the biochar of the modified sulfoaluminate cement obtained in step (1) into the sulfoaluminate cement at an addition amount of 1 wt%, and mix them dry to obtain the modified sulfoaluminate cement.
[0059] Example 4
[0060] This example provides a biochar of modified sulfoaluminate cement and a preparation method of modified sulfoaluminate cement.
[0061] (1) Preparation of biochar of modified sulfoaluminate cement:
[0062] Crush the iron-containing sludge cake to obtain iron-containing sludge residue, and crush the fruit wood and pass it through a 20-mesh sieve to obtain fruit wood residue. Mix the iron-containing sludge residue and the fruit wood residue at a mass ratio of 1:1, and mix the mixture of the two with water at a mass ratio of 1:10, and stir well to obtain a sludge-fruit wood residue suspension.
[0063] Put the sludge-fruit wood residue suspension into a reaction kettle, heat it to 230 °C at a heating rate of 5 °C / min for hydrothermal carbonization reaction, the reaction time is 4 h, the stirring rate is 400 rpm, and then cool it with circulating water. Filter and dry the hydrothermal product to obtain dry hydrothermal carbon.
[0064] Put the obtained dry hydrothermal carbon into a tube furnace and pyrolyze it under a nitrogen atmosphere. The heating rate is 10 °C / min, the target temperature is 800 °C, and after holding for 2 h, it is naturally cooled to room temperature to obtain hydrothermally pyrolyzed carbon, that is, the biochar of modified sulfoaluminate cement. The schematic diagram of the preparation process is as Figure 1 shown.
[0065] (2) Preparation method of modified sulfoaluminate cement:
[0066] Mix the biochar of the modified sulfoaluminate cement obtained in step (1) into the sulfoaluminate cement at an addition amount of 1 wt%, and mix them dry to obtain the modified sulfoaluminate cement.
[0067] Comparative Example 1
[0068] In this comparative example, the sulfoaluminate cement is not modified.
[0069] Comparative Example 2
[0070] The difference between this comparative example and Example 1 is that the hydrothermal reaction step is not performed in this comparative example, and the rest is the same as Example 1. The specific preparation process of biochar modified by sulphoaluminate cement in this comparative example is as follows:
[0071] The iron-containing sludge cake was crushed to obtain the iron-containing sludge residue, and the fruit wood was crushed and passed through a 20-mesh sieve to obtain the fruit wood residue. The iron-containing sludge residue and the fruit wood residue were mixed at a mass ratio of 1:1, and then dried at 80°C for 12 hours.
[0072] The dried mixture was placed in a tubular furnace for pyrolysis under a nitrogen atmosphere with a heating rate of 10°C / min and a target temperature of 800°C. After being kept warm for 2 hours, it was naturally cooled to room temperature to obtain pyrolytic carbon.
[0073] Comparative Example 3
[0074] The difference between this comparative example and comparative example 2 is that the holding time of pyrolysis is 4h.
[0075] Comparative Example 4
[0076] The difference between this comparative example and Example 1 is that the pyrolysis step is not performed in this comparative example, and the remaining steps are the same as those in Example 1. The specific preparation process of the biochar modified by sulphoaluminate cement in this comparative example is as follows:
[0077] The iron-containing sludge cake is crushed to obtain iron-containing sludge residue, and the fruit wood is crushed and passed through a 20-mesh sieve to obtain fruit wood residue. The iron-containing sludge residue and the fruit wood residue are mixed at a mass ratio of 1:1, and the mixture is mixed with water at a mass ratio of 1:10, and fully stirred to obtain sludge fruit wood residue turbid liquid.
[0078] The turbid liquid of sludge and fruit wood residue is placed in a reactor and heated to 200°C at a heating rate of 5°C / min for hydrothermal carbonization reaction. The reaction time is 2h and the stirring rate is 400rpm. It is then cooled by circulating water. The hydrothermal product is filtered and dried to obtain dry hydrothermal charcoal, i.e., biochar of modified sulphoaluminate cement.
[0079] Comparative Example 5
[0080] The difference between this comparative example and comparative example 4 is that the reaction time of the hydrothermal carbonization reaction is 4 hours.
[0081] Comparative Example 6
[0082] The difference between this comparative example and Example 1 is that this comparative example does not contain iron-containing sludge residue, and the missing part is supplemented by fruit wood residue.
[0083] Comparative Example 7
[0084] The difference between this comparative example and Example 1 is that this comparative example does not contain fruit wood residue, and the missing part is supplemented by iron-containing sludge residue.
[0085] Comparative Example 8
[0086] Compared with Example 1, the difference in this comparative example is that the pyrolysis temperature is 600 °C.
[0087] Comparative Example 9
[0088] Compared with Example 1, the difference in this comparative example is that the pyrolysis temperature is 1000 °C.
[0089] Comparative Example 10
[0090] Compared with Example 1, the difference in this comparative example is that during the preparation of the modified sulfoaluminate cement, the addition amount of biochar in the modified sulfoaluminate cement is 3 wt%.
[0091] Test Example
[0092] The modified sulfoaluminate cements of Examples 1 to 4, Comparative Examples 2 to 10, and the sulfoaluminate cement of Comparative Example 1 were made into concrete sample blocks for performance testing. The preparation method of the concrete sample blocks is as follows: 450 parts of unmodified or modified sulfoaluminate cement, 202.5 parts of water, and 1350 parts of standard sand.
[0093] The concrete sample blocks were placed in a standard testing machine, and a cement mortar compressive test was carried out on the concrete sample blocks. The loading speed was 2.4 kN / s, and the loading method was a single experiment to break the blocks to obtain the compressive strength. The results are summarized in Table 1.
[0094] Table 1 Performance test data of concrete sample blocks in examples and comparative examples
[0095]
[0096] Compared with Comparative Example 1, the compressive strength of the concrete sample blocks in Examples 1 to 4 increased slightly from 1 to 7 days. When it reached the 28th day, the compressive strength of the concrete sample blocks in the examples continued to increase, but the compressive strength of the concrete blocks in Comparative Example 1 decreased significantly. The compressive strength of the concrete samples in the examples was significantly higher than that in Comparative Example 1, indicating that the addition of hydrothermal pyrolysis carbon can continuously increase the compactness of the sulfoaluminate cement hydration paste, alleviate the phenomenon of late strength retrogression caused by the decrease in structural compactness, and thus achieve the goal of continuously enhancing the late strength of the sulfoaluminate cement.
[0097] The compressive strength of Comparative Example 2 decreased compared to that of Example 1. The reason is that the formation of the aromatic carbon skeleton during the hydrothermal process in Example 1 avoided the large volatilization of organic matter during the direct pyrolysis process, reducing the adverse effects of volatilization on the carbon skeleton. The extension of the pyrolysis holding time in Comparative Example 3 increased the pore structure to a certain extent, and the compressive strength increased compared to Comparative Example 2. Since there was no pyrolysis step in Comparative Example 4, the pore structure of the hydrothermal carbon was not enhanced, so the compressive strength decreased compared to Example 1. Compared with Comparative Example 4, the holding time of hydrothermal treatment in Comparative Example 5 was extended, causing more organic matter to dissolve into the liquid phase, damaging the carbon structure to a certain extent, and resulting in a decrease in the compressive strength of Comparative Example 5. Since iron-containing sludge was not added in Comparative Example 6, the promoting effect of iron during the cement hydration process could not be exerted, so the compressive strength decreased compared to Example 1. Compared with Example 1, the compressive strength of Comparative Example 7 decreased mainly because Comparative Example 7 did not contain fruit wood residue, and the cellulose components of the fruit wood residue could not be converted into an aromatic carbon skeleton. Compared with Example 1, the pyrolysis temperature in Comparative Example 8 decreased, resulting in a decrease in the porosity of the carbon material and a decrease in the compressive strength. Compared with Example 1, the pyrolysis temperature in Comparative Example 9 increased to 1000 °C. The excessively high pyrolysis temperature would cause the carbon skeleton to break and collapse, resulting in a decrease in the porosity and thus a decrease in the compressive strength. Compared with Example 1, adding an excessive amount of modifier in Comparative Example 10 would deteriorate the interfacial transition zone (ITZ) between the carbon particles and the cement matrix, weakening the overall strength of the concrete.
[0098] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A method for preparing biochar for modified sulphoaluminate cement, characterized in that: The steps include: The fruit wood residue and iron-containing sludge are mixed, water is added and a hydrothermal reaction is carried out at 200-250°C. After the reaction is completed, the mixture is filtered and dried to obtain a hydrothermal carbon material. The hydrothermal carbon material is then pyrolyzed in an inert atmosphere at a pyrolysis temperature of 700-900°C to obtain biochar of modified sulphoaluminate cement.
2. The preparation method according to claim 1, characterized in that The fruit wood residue is sieved, and the sieve size is 18 to 50 meshes.
3. The preparation method according to claim 1, characterized in that: The mass fraction of the iron element in the iron-containing sludge is 1-3%, and the water content of the iron-containing sludge is 60-90%.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the fruit wood residue to the iron-containing sludge is 1:(0.8-1.2).
5. The preparation method according to claim 1, characterized in that: The hydrothermal reaction time is 2 to 4 hours.
6. The preparation method according to claim 1, characterized in that: In the pyrolysis step, the pyrolysis temperature is 750-850° C. and the pyrolysis time is 1.5-3 hours.
7. The preparation method according to claim 6, characterized in that: The heating rate from the temperature rise to the pyrolysis temperature is 5 to 15°C / min; the inert atmosphere is selected from one or more of nitrogen or rare gases.
8. Biochar for modified sulphoaluminate cement prepared by the preparation method according to any one of claims 1 to 7.
9. A modified sulphoaluminate cement, characterized in that: The invention comprises sulphoaluminate cement and 0.5-2 wt % of the biochar of the modified sulphoaluminate cement according to claim 8.
10. The method for preparing modified sulphoaluminate cement according to claim 9, characterized in that: The steps include: The sulphoaluminate cement and the biochar of the modified sulphoaluminate cement are dry-mixed to obtain the biochar.
Citation Information
Patent Citations
A modified sulfoaluminate cement, its preparation method and application
CN112608047B
A preparation method of lithium salt modified sulphoaluminate cement and its products
CN117401917B